An exploratory investigation of investments and economic development in Saudi Arabia - Jones, AbdulHafiz Henry James (Archives of Business Research, 2019)
This proposal highlighted the key areas that warrant further investigation at a more granular level. There is an underlying question that must be answered. This question requires in-depth analysis of the GDP, GDP contribution structure, real GDP growth, foreign and domestic investment inflows, and outflows. Furthermore, an in-depth investigation on the nature of foreign and domestic investment inflows and outflows to include FDI, import and exports, intellectual property receipts and payments as well as other balance of payment investment line-items.